Income inequality and psychological distress at neighbourhood and municipality level: An analysis in the Netherlands. (March 2019) - Erdem, Özcan; Van Lenthe, Frank J.; Burdorf, Alex
Abstract: This study examines the associations between income inequality at neighbourhood and municipality level and psychological distress in a country with a relatively low income inequality, the Netherlands. Multilevel linear regression analyses were used to investigate associations between income inequality and mean income at the neighbourhood (n = 7803) and municipality (n = 406) level and psychological distress (scale range 10–50), in a country-wide sample of 343, 327 individuals, adjusted for gender, age, ethnicity, marital status, education and household income. No significant association was found between neighbourhood income inequality and psychological distress after adjustment for individual and neighbourhood level confounding. However, a higher neighbourhood income inequality in neighbourhoods with the middle to highest mean neighbourhood incomes was associated with more psychological distress. Individuals living in municipalities with the highest income inequality reported 2.5% higher psychological distress compared to those living in municipalities with the lowest income inequality. Income inequality seems to matter more for mental health at the municipality than neighbourhood level. Highlights: Results on income inequality in small areas and mental health are mixed. Mental health effects of neighbourhood income inequality depend on neighbourhood income. Municipal income inequality is more important as a risk factor for mental health than municipal income.